Prevention of Mother to Child Transmission (PMTCT) Program at Paropakar Maternity and Women’s Hospital: A Review - Shrestha, M; Chaudhary, P; Tumbhahangphe, M; Poudel, J (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: Vertical transmission from mother to fetus is the main route of HIVinfection among children. This study is an effort to review utilization of prevention of mother to child transmission (PMTCT) services by pregnant women seeking care in Paropakar Maternity and Women’s Hospital (PMWH). Methods: Case records of 165 pregnant women with HIV positive status who delivered at Paropakar Maternity and Women’s Hospital, Kathmandu from April 2005 to Dec 2011 were reviewed. Demographic profile of these women and interventions to prevent mother to child transmission (MTCT) including antiretroviral prophylaxis (ARV), mode of delivery, infant feeding practice as well as HIV status of their children were recorded. Results: Hospital records showed 109262 antenatal attendees and 120823 deliveries including 165 HIV infected women who delivered in this facility. Prevalence of HIV infection among antenatal attendees was 0.11 % and 0.13% in hospital deliveries. Migrant worker spouse (44.2%) was the main source of infection in their wives. Eighty eight (55.7%) out of 150 eligible women received ARV drugs and 97% babies received antiretroviral prophylaxis . Spontaneous vaginal delivery occurred in 60% women and caesarean section performed in the rest. While 60.8% women opted for exclusive breast feeding, remaining 39.2% chose formula feeding. For prophylaxis of opportunistic infection, Cotrimoxazole was given to 70.3% children. The incidence of HIV infection in babies born to HIV infected mother was 5.1%. Conclusions: Integrating PMTCT services into existing maternal and child health system can significantly reduce perinatal transmission of HIV infection to children. DOI: http://www.dx.doi.org/10.3126/njog.v7i2.11138 Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 2 / Issue 14 / July-Dec, 2012 / 25-28